Mitigating methane emissions for rural tropical livestock through selecting appropriate grass types - Ridla, Muhammad; Asikin, Nevyani; Jayanegara, Anuraga; Samsudin, Anjas Asmara @ Ab Hadi (Fundacion CIPAV, 2023)
Livestock farming contributes significantly to greenhouse gas emissions, with ruminant production being a major contributor. Manipulating the nutrient content of the diet can affect methane emissions in ruminants. However, tropical grasses, which are crucial in the ruminant diet in tropical regions, have limited potential due to their high structural carbohydrate and low non-structural carbohydrate content. The study aimed to identify appropriate tropical grass species that produce less methane gas during rumen fermentation. Seven tropical grass species were tested for their proximate and cell wall compositions, sugar and starch contents, and in vitro rumen fermentation parameters, including total short-chain fatty acid (TSCFA) and methane production. ANOVA was used to analyze the data and the Duncan test was applied if there were (p<0.05) differences. The results showed variation (p<0.05) in nutrient content, including structural and non-structural carbohydrates, among the grasses. Brachiaria mulato grass was found to produce the lowest methane production (29.91 TSCFA) and had the highest total starch content (13.40 DM), with the lowest NDF (67.54 DM) and ADF (37.33 DM) among the selected tropical grasses. Conversely, grasses with high structural carbohydrate content, such as Panicum maximumvar. Trichoglume produced higher levels of methane (33.13 TSCFA)